Contribution to the Improvement of the Performances of Doubly Fed Induction Machine Functioning in Motor Mode By the DTC Control - Najib EL Ouanjli; Aziz Derouich; Abdelaziz El Ghzizal; Youness El Mourabit; Mohammed Taoussi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
In this article, we are interested in the improvement of the performances of Doubly Fed Induction Machine (DFIM) operating in motor mode by the use of the direct torque control (DTC). Firstly, we focused on the modeling of the DFIM and the study of the principle of functioning of the DTC control. Then, we implement this control on the Matlab/Simulink environment. Secondly, we present the simulation results of the proposed control. The analysis of these results shows clearly that the system based on the DFIM studied follows perfectly the set points, what allowed us to justify the efficiency of the elaborate control.